S70 Mesenchymal Stem Cell Conditioned Media (MSC-CM) Suppress Wnt-3A and TGF-β1-Induced Myofibroblastic Differentiation. (19th November 2012) - Samad, S; Akram, KM; Forsyth, NR; Spiteri, M
Abstract : Hypothesis: Idiopathic pulmonary fibrosis (IPF) remains an incurable fibrotic lung disease. A mesenchymal stem cell (MSC)-mediated regenerative approach has been proposed; MSC-mediated anti-fibrotic effects have been demonstrated in animal lung-fibrosis models. However the mechanism of action and effect on myofibroblastic differentiation are unknown. The Wnt family member, Wnt-3a, has been implicated as an inducer of myofibroblastic differentiation in fibroblast cell models. This study explores the influence of MSC secreted factors on Wnt-3a and TGF-β1-induced lung myofibroblastic differentiation. Method: Human normal lung (CCD-8Lu) and IPF (LL29) fibroblasts were differentiated with Wnt-3a for 72-hours and TGF-β1 for 24-hours. MSC-mediated differentiation inhibition was assessed by co-incubation of fibroblasts with MSC-CM and either Wnt-3a for 72-hours or TGF-β1 for 24-hours. TGF-β1-induced myofibroblastic differentiation reversal was explored with MSC-CM incubation for 24, 48 and 72-hours. Myofibroblast differentiation was assessed by immunocytochemical detection of α-smooth muscle actin expression. Results: Myofibroblastic differentiation following TGF-β1 treatment was achieved in 86.27+2.57% CCD-8Lu cells and 86.69+2.51% LL29 cells respectively. Similar, though reduced, levels of myofibroblastic differentiation were achieved in 52.9±0.2% CCD-8Lu and 55.6±5.9% LL29 cells respectively following Wnt-3a treatment. In contrast, a percentage reduction in myofibroblastic differentiation was achieved in CCD-8Lu 31.40+1.44% and LL29 35.69+7.47% cells following exposure to TGF-β1 in the presence of MSC-CM versus TGF-β1 alone (p<0.001). Similarly, we observed a striking percentage reduction in myofibroblastic differentiation following co-incubation with Wnt-3a and MSC-CM versus Wnt-3a alone (p<0.001); 80.76±3.64% of CCD-8Lu and 79.67±3.94% of LL29 cells. A reversal of TGF-β1-induced myofibroblastic differentiation was observed following 72-hours administration of MSC-CM compared to serum-free culture media (p<0.001). Interestingly, we observed a MSC-CM exposure duration effect on the total myofibroblast percentage present in both CCD8-Lu and LL29 cells; 81.7+0.43% and 73.26+0.70% respectively at 24-hours, 72.15+0.81% and 60.57+4.27% at 48-hours, 57.63+4.54% and 60.65+4.9% at 72-hours. Conclusion: MSC-CM appears to inhibit fibroblast to myofibroblast differentiation, over-riding the pro-differentiation effects of Wnt-3a and TGF-β1. Whilst both TGF-β1 and Wnt-3a have emerged as key players in IPF pathogenesis, we are the first to demonstrate that MSC-CM may be crucial in modulating their pro-fibrogenic effects. These actions of MSC-CM demonstrate exploitative potential for future anti-IPF therapeutic strategies.